Planning Design in Arabic Language Curriculum - Hilyah Ahya Muthmainnah; Isop Syafei (UIN Sunan Gunung Djati Bandung, 2025)
Arabic language learning has a strategic position in education, especially in Indonesia the largest Muslim country. For learning to be effective, careful and purposeful curriculum planning is required. This article aims to examine the design of curriculum planning in Arabic language learning, by highlighting the principles, foundations, stages, and management involved. This research uses a qualitative approach with a literature study method, namely through reviewing relevant literature related to the theory of Arabic curriculum planning and development. The study results show that Arabic curriculum planning must be based on the right educational philosophy, considering the needs of students, social demands, and scientific developments. The planning process includes setting goals, determining content, and methods, and evaluating integrated learning. In addition, the participation of teachers, students, and the community is an important element in curriculum decision-making. This study confirms that the success of Arabic language learning is largely determined by the quality of curriculum design that is contextual, realistic, and adaptive to changing times.